Recovery of muscle weakness and physical function in a patient with severe ICU‐acquired weakness following pulmonary embolism: A case report - Morimoto, Yosuke (Clin Case Rep, 2018)
Although ICU‐AW is a common condition in critically ill, it is unclear which intervention is best to treat. We applied combined exercise training and nutritional supplementation, and these were effective to recover the skeletal muscle function and exercise capacity. We should recognize necessity of nutritional support in ICU‐AW patients.